OPTIMALISASI PERTUMBUHAN DAN PERKEMBANGAN ANAK DENGAN MITIGASI STUNTING DAN PENGUKURAN DENVER DEVELOPMENT SCREENING TEST (DDST) PADA ANAK BALITA - Syafitri, Endang Nurul; Deny Krisnanto, Paulinus; Asmarani, Fajarina Lathu; Mindarsih, Eko; Tanjung, Sri (Jurnal Abdimas Bina Bangsa, 2025)
Stunting is a serious public health problem in many countries, including in Indonesia. Based on prevalence data per 2021, the stunting rate of children under five in Sleman Regency is 6.92% or 3,445 children. This data was obtained based on the measurement of the nutritional status of 59,275 children. And in 2022 the stunting rate has decreased to 6.88%. Ngemplak District is one part of Sleman district. The purpose of this service is to find out the nutritional status of children, know the development of children and educate them so that there will be an increase. The method used in this service is to measure growth using a weight weighing device (Digital Scale), Microtoice, and Z Score. To measure child development, the Denver development screening test (DDST) is used. The results of the service were obtained by 29 child respondents, with the majority being female 55.2%, nutritional status with the stunting category as much as 10.34% and suspect child development 17.24%. Conclusion: There are children with stunted nutritional status and there are children with suspect development